Efficacy of teriparatide and denosumab combination treatment in a patient with atypical femoral fracture and Behçet's disease: a case report and review of the literature. Issue 1 (2nd January 2018) - Uehara, Masashi; Nakamura, Yukio; Takahashi, Jun; Isobe, Fumihiro; Ikegami, Shota; Suzuki, Takako; Uchiyama, Shigeharu; Kamimura, Mikio; Kato, Hiroyuki
Abstract: Atypical femoral fracture (AFF) has emerged as one of the most concerning issues in the management of osteoporosis. However, the surgical and other treatment methods for AFF have not been fully established. This study investigated the clinical outcomes of AFF in a patient with Behçet's disease after long-term bisphosphonate (BP) therapy and the therapeutic effects of denosumab and teriparatide after surgery. We enrolled a patient with a Behçet's disease receiving long-term BP therapy who was treated for AFF by surgical treatment plus denosumab and teriparatide. Right-sided AFF occurred in a 45-year-old male with Behçet's disease. Teriparatide and denosumab were started after surgical treatment. No fracture or other complications were recorded during the 18-month postoperative observational period and bone union with good callus formation was achieved in four months after surgery. Lumbar and hip bone mineral density and bone turnover markers were markedly improved during follow-up. This is the first study describing AFF in a patient with Behçet's disease being successfully treated by surgery and osteoporotic treatment. Based on our findings, postoperative combination therapy of denosumab and teriparatide may be an effective therapy for AFF in Behçet's disease.